Influence of demographic factors and local wisdom on exclusive breastfeeding behavior - Mardhiah, Ainal; Nasution, Decy Erni; Inayati, Rahmi; Nurlaili, Nurlaili; Daud, Muhammad (Edelweiss Applied Science and Technology, 2024)
Exclusive breastfeeding from an early age is very important for a child's survival. The achievement of exclusive breastfeeding in Indonesia is still far from the target. There is a lot of research on the factors that influence exclusive breastfeeding, but there has been no research on the influence of local wisdom on exclusive breastfeeding especially in Pidie, Aceh, Indonesia. The aim of the research is to determine the influence of demographic factors and local wisdom on exclusive breastfeeding. Quantitative method with cross sectional study design was used in this research. The population was 3124 mothers’ breastfeeding babies aged 6 to 12 months in Pidie, Indonesia. Sample size was determined by Slovin formula with 95% convidence level so that the sample size to be 358 respondents. Data collection was done by distributing questionnaires or interviews. Univariate data analysis used to analyze all variables studied. Bivariate analysis used the chi square statistical test with SPSS 24. The research results show that 167 or 46.65% respondents provided exclusive breastfeeding. There is not influence of age, education, occupation, and food consumption on exclusive breastfeeding behavior. However, there is an influence of knowledge, dietary restrictions, postpartum care with local wisdom (such as sale and toet batee – refer to traditional treatment in Aceh) on exclusive breastfeeding. Health education is needed about the importance of exclusive breastfeeding and the effects of postpartum care with local wisdom on breast milk production.